2023
DOI: 10.1111/jocn.16806
|View full text |Cite
|
Sign up to set email alerts
|

Unmet supportive care needs of families of children with chronic illness: A systematic review

Abstract: Background and AimsUnmet supportive care needs (SCN) refer to perceived gaps in the support parents want to manage caregiving activities for children with chronic health conditions (CHC) and the support received. This review aims to systematically identify the unmet SCN of families with children living with five common paediatric CHC and characterise the assessment tools used to measure SCN.DesignSystematic review methodology with narrative synthesis of data. Reporting followed the PRISMA statement guidelines.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…These duties are often shouldered without prior training, adequate knowledge, or sufficient support systems. Pediatric nurses play a pivotal role in caring for children with cancer, frequently assuming the role of information providers and sources of support for both the child and their parents 50 . In the context of our study, we identified a significant negative correlation between the fulfillment of parents' needs and their stress levels.…”
Section: Discussionmentioning
confidence: 58%
“…These duties are often shouldered without prior training, adequate knowledge, or sufficient support systems. Pediatric nurses play a pivotal role in caring for children with cancer, frequently assuming the role of information providers and sources of support for both the child and their parents 50 . In the context of our study, we identified a significant negative correlation between the fulfillment of parents' needs and their stress levels.…”
Section: Discussionmentioning
confidence: 58%
“…Few studies to date have explored unmet needs in families of children with various CHCs ( Thomas et al, 2023 ). Moreover, few studies have examined links between unmet needs and parental distress in this population, with most work in this area to date focusing on parents of children with cancer ( Aziza et al, 2019 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the term "needs" refers to the speci c requirements of parents in terms of information. This includes the type, content, subject matter, quantity, frequency, and mode of delivery of information that parents either require or desire to effectively support and manage their children's health conditions (19,23).…”
Section: Phenomena Of Interestmentioning
confidence: 99%
“…Furthermore, the qualitative nature of the included studies introduces inherent limitations related to objectivity and comprehensiveness (6,17). A systematic analysis has underscored that family carers' supportive care requirements remain unmet, particularly in terms of access to critical information (e.g., treatment options, lifestyle recommendations) and health care services (e.g., emotional support, experiences with health care services) (19). Addressing these unmet needs is imperative to ensure the holistic well-being of both young patients and their families.…”
Section: Introductionmentioning
confidence: 99%